The Attentional Drift-Diffusion Model Extends to Simple Purchasing Decisions - Krajbich, Ian; Lu, Dingchao; Camerer, Colin; Rangel, Antonio (Frontiers in Psychology, 2012)
How do we make simple purchasing decisions (e.g., whether or not to buy a product at a given price)? Previous work has shown that the Attentional-Drift-Diffusion-Model (aDDM) can provide accurate descriptions of the psychometric data for binary and trinary value-based choices, and of how the choice process is guided by visual attention. However, the computational processes used to make purchasing decisions are unknown. Here we extend the aDDM to the case of purchasing decisions, and test it using an eye-tracking experiment. We find that the model provides a quantitatively accurate description of the relationship between choice, reaction time, and visual fixations using parameters that are very similar to those that best fit the previous data. The only critical difference is that the choice biases induced by the fixations are about half as big in purchasing decisions as in binary choices. This suggests that the brain uses similar computational processes in these varied decision situations.